Gaining Qualitative Insights Into Learners' Experiences And Perceptions Of Digital Activities For English Language Learning - Risnawati Risnawati; Safnil Arsyad; Dian Eka Chandra Wardhana (JETL (Journal of Education, Teaching and Learning), 2025)
The integration of digital activities into language learning has transformed traditional instructional methods, increasing engagement and interactivity. This study explores the experiences and perceptions of fourth-semester students in the English Education program at State Islamic University Fatmawati Sukarno Bengkulu regarding the use of digital tools for language acquisition. Employing a qualitative research design, the study investigates students’ evaluations of digital resources, their perceived benefits, and the challenges they encounter. Findings reveal that students frequently utilize digital tools such as educational videos, online reading platforms, and social media to enhance vocabulary acquisition, listening comprehension, and interactive language practice. Digital activities, particularly those incorporating gamification, are perceived as engaging and motivating. However, students also identify key challenges, including a lack of structured guidance, limited feedback, and technological barriers such as poor internet connectivity. While digital tools effectively support receptive skills (listening and reading), their impact on productive skills (speaking and writing) is limited without instructor support. This study contributes to research on digital learning by highlighting both its pedagogical advantages and constraints. The findings emphasize the need for structured pedagogical interventions, such as blended learning models that integrate digital tools with instructor-led guidance and feedback. Addressing technological barriers is also crucial to ensuring equitable access to digital learning resources. Future research should examine the long-term effects of digital learning on productive language skills and explore strategies for optimizing digital learning outcomes. By understanding students’ experiences, educators and institutions can refine digital learning approaches to enhance engagement and language acquisition.